The validity of simplifying gaming simulations - M.A. van Haaften; I. Lefter; O. van Kooten; F.M.T. Brazier (Computers in Human Behavior Reports, 2024)
Simplifications of the real world affect the validity and reliability of gaming simulations. This challenges the application of gaming simulations as an instrument for experiential learning, reflective practices and data collection. This study investigates the effects of simplification on extracting tacit knowledge from human behavior by answering the research question: Can tacit knowledge in a simplified design of a gaming simulation be transferred without compromising the validity and reliability corresponding to the real-world complexity? By applying a participatory design a gaming simulation is tested as an instrument to extract tacit knowledge. To test and evaluate the validity of this application, simulation sessions have been performed with experts from the field. In simplifying reality, participants' participation emphasized that the most accurate representation of reality is a prerequisite for capturing tacit knowledge. This in turn contributes again to the validity of the simulation design. The results show that simplification of the real world didn't affect participants' perspective on the use of the gaming simulation as an experiential tool to enable learning processes or create awareness. And that a simplified simulation design, is still valid in addressing the real-world complexity, with minimization of the level of abstraction and maximization of the truthfulness.